2020
DOI: 10.1186/s13023-020-01588-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical signs and symptoms of Behçet’s disease with mean platelet volume (MPV) and red cell distribution width (RDW)

Abstract: Background A strong correlation was previously found between mean platelet volume (MPV), red blood cell distribution width (RDW), and the severity of signs and symptoms in patients suffering from inflammatory and autoimmune diseases. The current study evaluated these correlations in patients with Behçet’s disease (BD) as well the relationship between MPV and RDW and disease activity score on the Iranian Behçet’s Disease Dynamic Activity Measurement (IBDDAM). Methods This cross-sectional study included 319 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Moreover, a high C-reactive protein (CRP)/albumin (ALB) ratio (CAR) was found to be associated with poor outcome of cancer patients, and this marker could be used as a predictor of poor cancer prognosis (8). To date, many extensive studies have been conducted on the effects and use of NLR, CAR, and mean platelet volume (MPV) in disease progression and prognosis, such as psoriasis, rheumatoid arthritis, systemic lupus erythematosus, Behçet's syndrome, and Sjögren syndrome (7,(9)(10)(11)(12). However, there are very few studies on the significance of these markers in AAV.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high C-reactive protein (CRP)/albumin (ALB) ratio (CAR) was found to be associated with poor outcome of cancer patients, and this marker could be used as a predictor of poor cancer prognosis (8). To date, many extensive studies have been conducted on the effects and use of NLR, CAR, and mean platelet volume (MPV) in disease progression and prognosis, such as psoriasis, rheumatoid arthritis, systemic lupus erythematosus, Behçet's syndrome, and Sjögren syndrome (7,(9)(10)(11)(12). However, there are very few studies on the significance of these markers in AAV.…”
Section: Introductionmentioning
confidence: 99%
“…An increased MPV has been associated with an increased thrombotic disposition (26,27). A higher MPV in patients with active BD has also been reported (28). Ataş et al (11) evaluated the effect of colchicine on MPV levels, and after colchicine treatment, a decrease in MPV was obtained in their study.…”
Section: Discussionmentioning
confidence: 73%
“…The possible explanation is that inflammation might lower erythrocyte survival and, in fact, promote anisocytosis, causing immature erythrocytes in larger volumes to enter the blood flow and an increased RDW [ 23 , 24 ]. In Behcet's disease (BD), a chronic systemic inflammatory disease, Masoumi et al discovered RDW levels were significantly higher in BD patients with any ocular manifestations and increased RDW level was significantly correlated with the risk of developing ocular diseases in BD patients (OR = 2.031, 95% CI: 1.572–2.625; p < 0.001), suggesting that elevated RDW may be related to the ocular vascular inflammation [ 25 ]. Aksoy et al also found an association between RDW and BD ocular activity, supporting the results of Masoumi et al [ 26 ].…”
Section: Discussionmentioning
confidence: 99%